Comparison of Behavior, Histology and ImpL2 Gene Expression of Octopus sinensis Under Starvation and Senescence Conditions - Bian, Li; Li, Fenghui; Chang, Qing; Liu, Changlin; Tan, Jie; Zhang, Shengnong; Li, Xuemei; Li, Meishuai; Sun, Yikang; Xu, Rongjing; Chen, Siqing (Frontiers in Marine Science, 2022)
Offshore cephalopods usually experience a short and extreme senescence process at the end of their lives. Unique behaviors such as brooding and fasting occur during this period. The cause of senescent cephalopod death is still unknown. Excessive energy consumption under prolonged starvation is one possible reason for death. A comparison analysis between normal starvation and senescence may provide valuable information to deepen our understanding of the senescence process of cephalopods. In this study, a comparison of behavior, histology and expression of a candidate senescence-specific gene (Imaginal morphogenesis protein-Late 2, ImpL2) of female Octopus sinensis under normal starvation and senescence was conducted. The females in the starvation group had similar behaviors, histology and ImpL2 expression level to the control group. The females in the senescence group exhibited typical behaviors and symptoms of senescent octopus, including fasting and unhealed lesions on the skin. Moreover, swimming and grasping ability was weakened in senescent individuals. The muscle tissue in the mantle and arm of senescent females showed a histolytic appearance. The secretory cells and their microvilli in the digestive gland gradually degraded and disappeared during senescence. The expression level of ImpL2 gene significantly changes in multiple organs of senescent females. The results showed that O. sinensis underwent different physiological and molecular processes during starvation and senescence. Starvation alone could not lead to senescent symptoms in the octopus. Tissue degeneration in the mantle, arm and digestive gland would increase the death risk of the octopus.